A study of the Distributional Peculiarity of /l/ Allophony for Advanced Iraqi Girl Students at Teachers preparatory Institute: A Contrastive Experimental Analysis - Haifa Adnan Salman Al-kanaan (PROSPECTIVE RESEARCHES, 2023)
The purpose of this paper is to argue that not all learners' errors in L2 are necessarily the result of their L1 interference. In fact, many of these errors may be attributed to reasons other than the make-up of their L1. This argument is applied to the advanced Iraqi student teachers' (AIST) errors in the distributional allophony of /l/. The results obtained show that the learners' errors are the result of: - Analogy, i.e. applying L2 patterns into areas in which they cannot be applied. - Habitual mistakes; those which are so strongly fossilized from an early age that cannot be easily corrected later. - Systematic resistance to L1 patterns which correspond to L2 ones. - Vocabulary problems resulting in whole-word mispronunciations. Such reasons and others are found to be behind learners' errors as regards this allophony, which in the light of the study is meant to analyze the subjects' performance of a chosen material depending on the contrastive analysis (CA) results. The study also presents suggestions to solve some of these problems. The experimental procedures are carried out depending on the voluntary participation of the fifth-year students, Dept. of English in the Teacher Training Institute/ Nineveh of the academic year 2012-2013.